If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + 1) = 2(x + -3) Reorder the terms: (1 + y) = 2(x + -3) Remove parenthesis around (1 + y) 1 + y = 2(x + -3) Reorder the terms: 1 + y = 2(-3 + x) 1 + y = (-3 * 2 + x * 2) 1 + y = (-6 + 2x) Solving 1 + y = -6 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = -6 + -1 + 2x Combine like terms: 1 + -1 = 0 0 + y = -6 + -1 + 2x y = -6 + -1 + 2x Combine like terms: -6 + -1 = -7 y = -7 + 2x Simplifying y = -7 + 2x
| 9c-15=4c | | 8(4x+1)=9(5x-2) | | 10x^9-17x^7+7x^6= | | 5x-1/2x=18 | | 5(x-90)-4(x+150)=950 | | x+x/2+4=30 | | 8(d+5)=23 | | 4x^2+8-12=0 | | n^2+8=-6n | | 3(7+c)=60 | | 52000-8n=18000+8n | | 8(4x+1)=14(2x-3) | | [3(m-5)+16]-[2(3m-3)+5]= | | -3+5(2x-17)=1 | | a(x-a)=1 | | 3(7+c)=51 | | w/4.3-9.8=70 | | 7-6u=5u+19 | | 4n-3n+2=5 | | 4-9x=4x+27 | | -17+6x-2x=11 | | 4(3x+8)-4=7(2x-1)+3x | | 12a^6b^6+6ab^4-30ab^6= | | 2r-9=13 | | 5x-1=3(x)+9 | | (2-3a)/4=5 | | (4/x)=(1/4)x | | P+3Y=164 | | (2-3a)/45 | | -1+8(1+4x)=199 | | 5x+125-x=100 | | -10x+9y=-2 |